METHODS FOR TREATING AND/OR PREVENTING GRAFT-VERSUS-HOST DISEASE AND/OR DIFFUSE ALVEOLAR HEMORRHAGE AND/OR VENO-OCCLUSIVE DISEASE ASSOCIATED WITH HEMATOPOIETIC STEM CELL TRANSPLANT - SCHWAEBLE, Hans-Wilhelm; DEMOPULOS, Gregory A; DUDLER, Thomas (2025)
In one aspect, the invention provides methods of inhibiting the effects of MASP-2-dependent complement activation in a human subject suffering from graft- versus-host disease and/or diffuse alveolar hemorrhage and/or veno-occlusive disease associated with a hematopoietic stem cell transplant. The methods comprise the step of administering, to a subject in need thereof, an amount of a MASP-2 inhibitory agent effective to inhibit MASP-2-dependent complement activation.